The Role of Health Literacy on Adolescent Smoking Behavior in Senior High School - Elmiana Bongga Linggi; Yunita Gabriela Madu; Darma Caesaria Daben; Desi Tandi (Jurnal Ilmiah Ilmu Keperawatan Indonesia, 2022)
Background: Smoking is a behaviour that's not foreign to the public, especially for teenagers. Smoking can hurt the health of all people, including adolescents. Health literacy is a cognitive and social skill for a person to improve their ability health. Objectives: To determine the relationship between health literacy and smoking behavior in adolescents. Methods: The research design used quantitative descriptive with a cross-sectional approach, the respondents were teenagers with a total 0f 83 respondents who were willing to fill out the questionnaire. Data analysis using frequency distribution and Chi-Square test. Results: The Result shows a most of the respondents were in the age category of 16 years (25,3%) and 16 years, The health literacy level of respondents was mostly in the able category is 83.1% and in the smoking behavior of respondents in the no category is 62.7%.Chi Square analysis result is p value is 0,000smaller then α there is health literacy relaed to smooking behavior in adolescents . Conclusion: Health literacy can be used as a strategy to reduce smoking behaviour in adolescents.